Penyuluhan Pencegahan Pelecehan Seksual pada Anak Sekolah Dasar - Sasmita, Ruwaiza; Melina, Angra; Fathullah Saputra, Dipo (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
Child sexual abuse is a serious problem that can have a long-term impact on the psychological development of victims. This counseling aims to increase children's awareness and understanding of the dangers of sexual harassment and how to protect themselves. The activity was carried out at SD Negeri 03 Merangin Regency through an interactive socialization method with a story-telling approach, discussion, and educational games. The results of the activity showed an increase in participants' understanding of body limitations, types of inappropriate touch, and steps to take if they experience harassment. This counseling is expected to be a preventive step in preventing cases of sexual harassment in the school environment.